Survival and development of Cadra cautella (Walker) (Lepidoptera: Pyralidae) on cocoa bean and cocoa powder: Kemampuan hidup dan perkembangan Cadra cautella (Walker) (Lepidoptera: Pyralidae) pada biji dan bubuk kakao - Astuti, Ludji Pantja; Sartika, Putri Dewi; Mutala'liah, Mutala'liah; Wulandari, Ratna; Ramadhan, Nino Trifatu (Perhimpunan Entomologi Indonesia, 2024)
The almond moth Cadra cautella (Walker) is a notable stored product pest which can cause detrimental loss on stored cocoa. Cocoa can be stored in bean and powder forms. The information about survival and development of C. cautella on stored cocoa is limited. This research aimed to determine the effect of cocoa powder and cocoa bean in the storage against the survival and development of C. cautella. This research was conducted in Plant Pests Laboratory, Department of Plant Pests and Diseases, Faculty of Agriculture, Universitas Brawijaya. This research consisted of two treatments namely cocoa bean and cocoa powder with no choice method and repeated six times. The observed variables were number of larvae, pupae, male and female almond moth of F1 progeny, and developmental time of this insect. The t-test analysis was applied to determine the treatment effect. Results showed that the number of larvae, pupae, adult males and females of F1 progeny cultured on cocoa powder were significantly higher than on cocoa bean. The total developmental time and life cycle of almond moth were shorter on cocoa powder than on cocoa bean. Therefore, to store cocoa in powder form is riskier to the almond moth infestation rather than in bean form. Hence, it is suggested to take more concern on the cocoa powder storage better in order to minimize the almond moth infestation.